Sexual maturity and Sexual dimorphism in a population of the rocket-frog Colostethus aff. fraterdanieli (Anura: Dendrobatidae) on the northeastern Cordillera Central of Colombia (2015)
ABSTRACT: The minimum size of sexual maturity and sexual dimorphism are important life history traits useful to study and understand the population dynamics of any species. In this study, we determined the minimum size at sexual maturity and the existence of sexual dimorphism in a population of the rocket-frog, Colostethus aff. fraterdanieli, by means of morphological and morphometric data and macro and microscopic observation of the gonads. Females attained sexual maturity at 17.90 ± 0.1 mm snout-vent length (SVL), while males attained sexual maturity at 16.13 ± 0.06 mm SVL. Females differed from males in size, shape and throat coloration. Males were smaller than females and had a marked and dark throat coloration that sometimes extended to the chest, while females lacked this characteristic, with a throat either immaculate or weakly pigmented. In this study, we describe some important aspects of the reproductive ecology of a population of C. aff. fraterdanieli useful as a baseline for other more specialized studies.